2018
DOI: 10.1371/journal.pone.0197491
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of calcineurin 1 differentially regulates TLR-dependent MyD88 and TRIF signaling pathways

Abstract: Toll-like receptors (TLRs) recognize the conserved molecular patterns in microorganisms and trigger myeloid differentiation primary response 88 (MyD88) and/or TIR-domain-containing adapter-inducing interferon-β (TRIF) pathways that are critical for host defense against microbial infection. However, the molecular mechanisms that govern TLR signaling remain incompletely understood. Regulator of calcineurin-1 (RCAN1), a small evolutionarily conserved protein that inhibits calcineurin phosphatase activity, suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…3A-C) (38,39) and Rcan1 (SFig. 3D-F) (40), as well as a previously uncharacterized inflammatory specific isoform of Ampd3 (SFig. 3G-I), in human and mouse primary macrophages using RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…3A-C) (38,39) and Rcan1 (SFig. 3D-F) (40), as well as a previously uncharacterized inflammatory specific isoform of Ampd3 (SFig. 3G-I), in human and mouse primary macrophages using RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…It had been suggested that DEN-induced liver injury was accompanied by elevation of plasma LPS level, and then LPS can transiently exaggerated DEN-induced liver damage (Yu et al, 2010). After binding to TLR4, two critical intracellular signaling pathways are triggered, including the myeloid differentiation primary response 88 (MyD88) dependent and MyD88-independent signaling cascades (Pang et al, 2018). The MyD88-dependent signal transduction activates NF-κB through activation of its inhibitory protein IκBα, which allows NF-κB nuclear translocation and controls the expression of a multitude of proinflammatory cytokines and other immune-related genes, such as TNF-α, IL-1, IL-1β, IL-6, and IL-12 (Shi et al, 2013; Li X. et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…MyD88 activates the nuclear factor kappa light chain enhancer of activated B cells (NF-κB), allowing the activation of a multitude of pro-inflammatory cytokines and chemokines (IL-6, TNF-α, and the macrophage inflammatory protein (MIP)-2). TRIF drives the transcription of chemokines IFN-α and IFN-β, RANTES (regulated in the activation of normal expressed and secreted T cell expressed) and IP-10 (Interferon γ-inducible protein 10) [60]. A TLR4/MD2 agonistic monoclonal antibody, UT12, promoted host defence against chronic P. aeruginosa lung infection in mice, increasing neutrophil levels and concentrations of inflammatory MIP-2 in the lungs and improving bacterial clearance [61].…”
Section: Host Immune Response Against P Aeruginosamentioning
confidence: 99%